GAMBARAN KONSELING DARING SELAMA PANDEMI COVID-19 - Linda Wati; Untung Subroto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Covid-19 pandemic has not only had an impact on physical health, but also mental health. This impact can not only be experienced by health workers, but also community. Online counseling is considered the right intervention during Covid-19 pandemic because it makes individuals do not meet in person and can minimize the risk of transmitting the virus. Online counseling is considered to be able to reduce the negatic impact of the effect of Covid-19 on psychological health. This research was conducted on 17 subjets who become clients in online counseling held by a psychological consulting bureau without being charged a counseling fee. The study was conducted from February to November 2021. The study found that the problems that needed assistance in counseling were problems hat dit not mention Covid-19 as he source of the problem. The problem they complain about tends to their attitude in dealing ith environmental demands which have been experienced or formed before the pandemic occurred.